Penerapan Media Pembelajaran Kahoot untuk Meningkatkan Minat Belajar Siswa pada Mata Pelajaran Informatika di MTsN 9 Kuningan Kelas VII - Husaini, Mochammad Fahri Akbar; Gustiana, Eva (Lembaga Intelektual Muda (LIM) Maluku, 2024)
This study aims to find out the extent of the application of kahoot media in increasing students' interest in learning informatics subjects in MTsN 9 Kuningan school. The research method used is a quantitative method. The design used was quasi-experimental which was part of the experimental method, this study grouped the respondents into two parts, namely the first class as an experimental class that was given treatment using Kahoot media and the second class as a control class that was given treatment using conventional learning. The instrument in this study is in the form of a questionnaire that uses kahoot media which has previously been tested for validity and reliability. Data analysis includes normality and homogeneity tests, linearity and the use of paired sample t-tests. The results of this study indicate that there are differences in terms of increasing the learning interest of students taught using conventional learning methods with students taught using kahoot learning media. The use of kahoot learning media in learning Informatics class VII MTsN 9 Kuningan is better than conventional media. This is evidenced by the results of the pretest and posttest questionnaire calculations for the experimental class, the pretest was 71.44 and the posttest was 80.25. This shows a significant increase in student interest in learning after the kahoot learning media treatment with an increase value of 5.81